Analisis Usahatani Perkebunan Kelapa Sawit Rakyat Berdasarkan Jasa Ekosistem Pengaturan Tata Aliran Air dan Banjir di Provinsi Riau - Riati Bakce; Riyadi Mustofa (Pelantar Press, 2023)
Riau Province has the largest oil palm plantation in Indonesia consisting of large national private plantations and community plantations located in various land typologies and landscapes. Each landscape has characteristics of forest areas and peat hydrological units that can affect the level of land productivity. This study aims to determine the carrying capacity of environmental capacity based on ecosystem services of water flow and flood management services in smallholder oil palm plantations in Riau Province. The analysis method consists of spatial analysis and farming analysis, spatial analysis to determine the carrying capacity of environmental capacity based on ecosystem services for water flow and flood management services. Farming analysis to determine land productivity, fresh fruit bunch (FFB) prices, production costs and farmer income based on environmental capacity criteria based on ecosystem services for water flow and flood management services. The results showed that based on the capacity of environmental capacity based on ecosystem services for water flow and flood management services on smallholder oil palm plantations in Riau Province consisted of very low, low, medium, high and very high criteria. Furthermore, the level of productivity, FFB prices, production costs and farmers' income are influenced by the typology of the capacity of water flow and flood management services. The higher the capacity of water flow and flood management services, the higher the land productivity and farmers' income.